1991
DOI: 10.1021/ie00049a004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of solvent and solute configuration on restrictive diffusion in hydrotreating catalysts

Abstract: Effective diffusivities of polyaromatic solutes in aliphatic solvents were determined from adsorption measurements a t ambient conditions with three hydrotreating catalysts of pore diameters 6.2-17.5 nm, Solutes studied were disklike (coronene, 9-phenylcarbazole, tetraphenylporphyrin, and tetra(4-biphenyly1)porphyrin) and rodlike (naphthalene, anthracene, benzanthracene, and dibenzanthracene) polyaromatics of critical dimensions ranging from 0.74 to 2.18 nm. A modified Wilke-Chang-type correlation was develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
2

Year Published

1993
1993
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 25 publications
1
21
2
Order By: Relevance
“…Centerline approximation appears accurate for diffusion of a sphere in a cylindrical pore. Configuration effects on hindered diffusion have been studied, and the results revealed that diffusivities of nonspherical solutes deviate to predicted values of spherical solutes 43–45. The difference between our results and those predicted from the Renkin equation might be a result of the configuration effect.…”
Section: Resultscontrasting
confidence: 60%
“…Centerline approximation appears accurate for diffusion of a sphere in a cylindrical pore. Configuration effects on hindered diffusion have been studied, and the results revealed that diffusivities of nonspherical solutes deviate to predicted values of spherical solutes 43–45. The difference between our results and those predicted from the Renkin equation might be a result of the configuration effect.…”
Section: Resultscontrasting
confidence: 60%
“…Configuration effects on hindered diffusion have been studied, and the results revealed that diffusivities of nonspherical solutes deviate to predicted values of spherical solutes. [43][44][45] The difference between our results and those predicted from the Renkin equation might be a result of the configuration effect.…”
Section: -40contrasting
confidence: 83%
“…In other words, the increased hindrance effects caused by the adsorbed solute layer would be reflected in an increased tortuosity value in the UPM. Tsai et al (1991) considered the experimental variation of tortuosity with molecule/pore size ratio and concluded that the use of a single average value of tortuosity up to ,1.0 = 0.35 was justified by their data. Smith (1986) has studied theoretically the effect of molecule/pore size on the tortuosity, finding the tortuosity variation to be a complex function of a pore constrictivity parameter.…”
Section: Diffusion Experiments and Model Simulationmentioning
confidence: 99%